Pengaruh Media Sosial Instagram terhadap Konstruksi Realitas Sosial pada Komunitas Mahasiswa Untirta - Praditia, Dennis Dita (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
In today's digital era, social media has become an inseparable part of daily life, especially for the younger generation. Among the various social media platforms, Instagram has become one of the most popular, especially among Untirta students. This media is not only used as a place to share photos and videos, but also as a space for social interaction, self-expression, and the search for information. However, behind its diverse functions, there are deep questions about the extent of Instagram's influence in shaping the social reality of the Untirta student community. This research uses a phenomenological approach, which is a way of building understanding of the reality experienced by someone, and that understanding is built from the subjects who live their activities in their lives. The focus of the phenomenological approach is how the subject interprets their personal experiences related to certain phenomena, experiences that are not just ordinary experiences, but experiences related to the structure of individual consciousness both directly and indirectly. Based on the research results and discussions conducted by the researcher, categorized into fan identity on social media, the construction of female fan identity of F.C. Barcelona, and fanaticism of F.C. Barcelona fans show that as a female fan of F.C. Barcelona, the interviewee wants to be seen as someone who truly supports F.C. Barcelona.